Music composition Of Hayuning Rasa | Tabuh Kreasi Hayuning Rasa - Kadek Agus Artana; I Wayan Suharta (Pusat Penerbitan LPPMPP ISI Denpasar, 2022)
Hayuning Rasa is a new creation of percussion that is still based on the existing tradition, then developed with a touch of creativity, both in terms of game technique, content, and parts of the song. By not eliminating musical elements, traditions, and adapting to the development of contemporary musical aesthetics, which are contained in the media, said Gamelan Gong Kebyar. This work has the theme of social life, which is inspired by life in a society that lives peacefully, happily and harmoniously which will be contained in the work of Tabuh Kreasi Hayuning Rasa. This cultivation method uses stages called Panca Sthiti Ngawi Sani. This stage will serve as a guide in creating a percussion creation of Hayuning Rasa, which consists of five stages: the inspiration stage (ngawirasa), the exploration stage (ngawacak), the conception stage (planning), the execution stage (ngawangun), the production stage (ngebah). The form of this work is the form and structure in the work of Tabuh Kreasi hayuning Rasa, which has various elements of musicality, accentuating the playing of instruments in each part, and the balance in this work is organized and arranged so that the relationship between parts can be realized and arranged systematically so that a work that has integrity. The structure consists of kawitan, crew and presses